Risk of bacteremia in hospitalised patients with inflammatory bowel disease: a 9-year cohort study. Issue 2 (March 2020) - Goren, Idan; Brom, Adi; Yanai, Henit; Dagan, Amir; Segal, Gad; Israel, Ariel
Background: Patients with inflammatory bowel disease might be at increased risk of invasive bacterial infections. Objectives: The objective of this study was to identify the rate of bacteremia in hospitalised patients with inflammatory bowel disease and risk factors. Methods: An observational cohort of hospitalised patients with inflammatory bowel disease, aged 16–80 years, from 2008 to 2017 in a large tertiary hospital. Patients with Charlson comorbidity index of 2 or greater were excluded. Patients with one or more positive blood culture were reviewed. Logistic regression was used to evaluate risk factors for bacteremia. Results: Of 5522 admitted patients, only 1.3% had bacteremia (73/5522) (39, Crohn's disease; 25, ulcerative colitis; nine, unclassified inflammatory bowel disease). The most common pathogen was Escherichia coli (19/73 patients). The mortality rate at 30 days of patients with bacteremia was 13.7% (10/73). Longer hospitalisations (mean length of stay (21.6 ± 31.0 vs. 6.4 ± 16.0 days; P < 0.0001) and older age (mean age 47.5 ± 18.0 vs. 40.2 ± 15.4 years, P < 0.0001)) were associated with an increased risk of bacteremia. In multivariate analysis, treatment with either anti-tumour necrosis factor α, purine analogues, steroids or amino salicylates was not associated with an increased risk of bacteremia. Risk was greatest among patients aged 65 years or older (relative risk 2.84, 95% confidence interval 1.6–4.8; P = 0.0001) relative to those under 65 years. Conclusion: Age over 65 years, but not inflammatory bowel disease-related medications, is associated with an increased risk of bacteremia in hospitalised patients with inflammatory bowel disease.